Postoperative bleeding after gastric endoscopic submucosal dissection in patients receiving antithrombotic therapy - Furuhata, Tsukasa; Kaise, Mitsuru; Hoteya, Shu; Iizuka, Toshiro; Yamada, Akihiro; Nomura, Kosuke; Kuribayashi, Yasutaka; Kikuchi, Daisuke; Matsui, Akira; Ogawa, Osamu; Yamashta, Satoshi; Mitani, Toshifumi (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2017)
Background and aims It is controversial whether antithrombotic therapy increases the risk of bleeding after endoscopic submucosal dissection (ESD). The aim of this study was to evaluate the effects of antithrombotic therapy on gastric ESD. Methods Patients who underwent gastric ESD at Toranomon Hospital between April 2005 and July 2014 were enrolled. The risk of post-ESD bleeding was evaluated by multivariate logistic regression analysis. Results Of 1781 patients enrolled, 253 were taking an antithrombotic; 186 discontinued taking a single antithrombotic ( n = 150) or multiple antithrombotics ( n = 36) before ESD, whereas 15 continued taking a single antiplatelet agent and another 52 switched to heparin alternative therapy during the peri-ESD period. Post-ESD bleeding occurred in 101 patients (5.7 %): 68 patients (3.8 %) who did not take an antithrombotic, 11 patients (7.3 %) who discontinued taking a single antithrombotic, six patients (16.7 %) who discontinued taking multiple antithrombotics, one patient (6.7 %) who continued taking a single antiplatelet agent, and 15 patients (28.8 %) who switched to heparin therapy. In multivariate analysis, heparin alternative therapy [odds ratio (OR) 10.04, 95 % confidence interval (CI) 4.35–23.16], discontinuation of the use of multiple antithrombotics before ESD (OR 5.44, 95 % CI 2.00–14.79), tumor location in the lower third of the stomach (OR 2.17, 95 % CI: 1.32–3.58), and a long procedure time (100 min or greater; OR 2.00, 95 % CI 1.25–3.20) were independent risk factors for post-ESD bleeding. Among 52 subjects who switched to heparin therapy, one developed acute renal infarction and one developed cerebral bleeding. Conclusions Because heparin alternative therapy significantly increases the risk of post-ESD bleeding and may not decrease the risk of thromboembolic events, other options should be considered for patients receiving anticoagulation therapy.